Green trail systems and tourism: improving the quality of life in Kansas City through the addition of green systems, connected districts and tourism opportunities - Wildhaber, Eric (Kansas State University, 2012)
The Mid America Regional Council, (MARC) is the official metropolitan planning organization for the Greater Kansas City region. MARC received a 4.25 million dollar grant from the US Department of Housing and Urban Development in 2010 to advance the region’s vision of sustainability through vibrant, green, and connected centers and corridors. From which the CSP (Creating Sustainable Places) initiative was established. Responding to this initiative, eight grant funded Kansas State University students worked in a Rock Island Corridor group. This group showed and described ways of achieving MARC’s and the US Department of Housing and Urban Development’s goals through the development of Master’s Reports. Reports include design ideas and proposals which MARC and city planning departments might not have developed otherwise. Student collaboration between public and city planning departments informed the development of student ideas. Green trail systems and tourism specifically addresses how the quality of life in the Kansas City Metro Area could be enhanced with the implementation of a cultural trail network. This network would provide access to the Rock Island Corridor, create greenspaces, and establish mixed-use housing districts for potential home and business owners. The Greater Kansas City region population is increasing. Trails, parks, and mixed-use buildings for residents in KC could improve the quality of life for future residents. Adding greenspaces, pedestrian mobility, and entertainment districts in which to find region specific activities could help attract people to redeveloping areas. Green trail systems and tourism’s project area is located between the Sprint Center and the Truman Sports Complex. To resolve problems and dilemmas within this region of Kansas City, a routing plan of a cultural trail network is outlined. This cultural trail features new trail heads, cultural centers, and proposed zoning overlays for park developments and mixed-use housing districts. The trail network created connects the Sprint Center and Truman Sports Complex in Kansas City, Missouri as a tourism link. Tourism destinations and historic sites add to the economic success of KC. Sites are connected to in the routing plan for the cultural trail. This proposal shows one approach for creating sustainable centers in KC.
Keywords: Urban trail; Neighborhood park; Kansas City; Creating sustainable places; MARC; Streetscape; Architecture (0729); Area Planning and Development (0341); Design (0389)